Implementation of The Special Arabic Language Learning Program (PKPBA) for New Student at The Tarbiyah and Teacher Training Faculty UIN Sultan Maulana Hasanuddin Banten | Implementasi Program Khusus Perkuliahan Bahasa Arab (PKPBA) Bagi Mahasiswa Baru Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasnauddin Banten - Dina Indriana; Ali Maksum (Mantiqu Tayr: Journal of Arabic Language, 2023)
The purpose of this study was to determine the implementation of the Special Arabic Language Learning Program at the Tarbiyah and Teacher Training Faculty of UIN SMH Banten. To determine the Arabic language skills of students at the Tarbiyah and Teacher Training Faculty of UIN SMH Banten. In this study, the researcher used a qualitative method design, which is a method that is often referred to as the naturalistic method because the research was carried out in natural conditions. The method, which is based on the philosophy of positivism, is used to examine the condition of a natural object where the researcher is the key instrument, sampling data sources is done purposively. The special Arabic learning program that the researchers will do is to focus on the Arabic language learning model for each department in the FTK environment by taking a sample of one major in one class. The results of the research are that in teaching second language material, you must understand the principles, namely the principle of priority, the principle of correctness and accuracy, the principle of gradation, the principle of emotionality and the principle of understanding the essence and multiplying applications in learning Arabic.